DEVICE AND METHODS FOR RESEARCH ROLLING FRICTION AND CONTACT ADHESIONE IN PRE-ROLLING - I. Z. Gilavdary; N. N. Riznookaya (Приборы и методы измерений, 2015)
Studies swing balls on flat substrate in pre-rolling, when the amplitudes of their oscillations are essentially less than radius of contact patch. A new phenomenological theory of rolling resistance is offered. This theory allows to determine moment of rolling resistance, friction coefficients, as well as determine the starting torque and the energy density of the peel adhesion. Describes the experimental setup and the experimental results, which are consistent with a mathematical model with high accuracy. In all the experiments gives estimates of accuracy.